Давні шляхи біля Давидового Броду на Інгульці - Каряка, О.В. (Археологія і давня історія України, 2021)
Стаття присвячена з’ясуванню ролі регіону села
Давидів Брід (Бериславський р-н, Херсонська обл.)
в системі суходільного сполучення між Інгульцем
та Дніпром та ключової ролі давніх курганів як
просторових орієнтирів у степових просторах. На
основі ретельного картографування та аналізу
супутникових знімків було виявлено місця максимальної концентрації давніх доріг та значну
роль досліджуваного регіону в системі сухопутної
комунікації Нижнього Подніпров’я у західному напрямку. In recent years, due to expansion of the capabilities
of using high-resolution satellite images and their
availability on many resources on the Internet, the
possibility of identifying new sites is becoming especially
relevant. In order to reveal the ability of land
communications as well as for the study of close relationship
of the barrows and steppe roads we made the
attempt to map them as completely as possible using
the remote sensing methods in the area between the
Dnieper and the Lower Ingulets Rivers.
The coverage of large territory made it possible to identify
the place of the highest concentration of road residues
which was located near the modern village of Davydiv Brid
(Beryslav district, Kherson region). There were three identified
so-called «Stars» — Bajdak-Mohyla, Shurzhyna and
Bilohirka. At the base of each of them was a large mound
of the 6—8 m high. All of them were in the line of sight
from one to another and marked the place of the traditional
crossing of the Ingulets River.
On the basis of the remnants of roads associated with
them the main directions of movement were identified:
1) the largest to the southeast to the area of the modern city
of Beryslav; 2) a less saturated but clearly traced eastern
route to the area of the modern Dudchany village; 3) along
the Ingulets valley on the top of the steppe plateau.
The internal structure and arrangement of the
mounds and remains of roads is very complicated and
can only be partially reconstructed. For example, we
consider the fact of the seasonal use of Shurzhin’s star
to bypass two lowlands located near Bajdak-Mogyla as
obvious. From the last point several direct routes of the
southeastern direction can be traced which were convenient
in the dry season.
The attempt to compare the roads identified by us
with the paths of the «three-verst Schubert map» of the
19th century had a few results. Only in some cases it is
possible to trace the coincidence of the historical paths
with those recorded by us in the southeastern direction
and only on certain sections. In the eastern direction
and the route along Ingulets there are no this kind of
coincidences were actually revealed.
As a result we consider it necessary to admit that the
remains of the roads we have recorded should be considered
a special type of archaeological monuments accompanying
other objects, primarily mounds. The phenomenon
of the remains of these roads and the «stars»
described by us is the phenomenon which reflects the
certain part of human activity in the past and should
be studied with the involvement of the as largest as
possible territories and conducting field research.